Does education shield against common mental disorders? - Edvard Johansson; Petri Böckerman; Tuija Martelin; Sami Pirkola; Kari Poikolainen (The Research Institute of the Finnish Economy (ETLA), 2009)
The paper examines the causal effect of education on common individual mental disorders in adulthood. We use a representative population health survey and instrumental variable methods. The estimates point to mostly insignificant effects of education on common mental disorders. We find that the length of education reduces the BDI (Beck Depression Inventory) measure at the 10% significance level, but has no effect when using the GHQ-12 (12-item General Health Questionnaire) or the probability of severe depression as a measure of mental health. These results cast doubt on the view that the length of formal education would be a particularly important determinant of common mental disorders later in life.
Keywords: I12; I21; 330; Education; Mental health; Common mental disorders; Bildungsabschluss; Bildungsniveau; Gesundheit; Psychische Störung; Instrumentalvariablen-Schätzmethode; Finnland